The Impact of AI on Endangered Languages: Can Technology Save or Kill? (Texas Journal of Philology, Culture and History, 2023)
This article examines the impact of artificial intelligence (AI) on endangered languages, assessing its potential to contribute to preservation or inadvertently accelerate decline. Beginning with a brief overview of the cultural significance of endangered languages, the article outlines challenges in preservation. It surveys historical preservation methods and introduces AI's role. Positive impacts of AI, such as documentation and revitalization, are discussed alongside concerns, including loss of authenticity. Through case studies, the article navigates successes and challenges. The central question, "Can Technology Save or Kill Endangered Languages?" is explored, emphasizing the delicate balance between technological aid and unintended consequences. The conclusion provides insights into the future of AI in language preservation and recommends responsible implementation. This article contributes to understanding the nuanced relationship between technology and endangered languages in academic discourse